Students’ Motivation in Learning Narrative Text Using STAD - Sulistiowati, Endang Retno; Taufiqulloh; Prihatin, Yoga (South Asian Journal of Social Sciences and Humanities, 2024)
This research is motivated by the low motivation to learn English among students in class VIII of SMP Negeri 3 Talang, so it is necessary to ncrease their motivation. The formulation of the type cooperative modelin class VIII at SMP Negeri 3 Talang. Theaim ofthis research is to determine students’ learning motivation in learning narrative text using the STAD type cooperative model. The literature review discussed includes STAD type cooperative learning and learning motivation. This research took place at SMP Negeri 3 Talang, Tegal Regency, which wascarried out from July 2023 to December 2023. The research population was251 students in class VIII of SMP Negeri 3 Talang 2023/2024. Samples were taken using cluster randomsampling, samples were obtainedfrom class VIIIA and VIIIC asthe experimental class and class VIIID as the control class. Data collection is carried out through questionnaries and documentation.Data analysis used the MANOVA test. The research results show that there is significant difference in students’ learning motivation in narrative text learning that uses STAD type cooperative model and those that do not in class VIII at SMP Negeri 3 Talang. The Percentage of learning motivation with STAD was 81.93% with very good criteria. Thisshows that students’learning motivationinlearning narrative text using STAD type cooperative model in class VIIIat SMPNegeri3 Talabg is better than without using STAD.